Implementasi Adaptasi Teknologi Di SDN Kedungdoro V Surabaya Melalui Kampus Mengajar 6 - Yulia Purni Fidiastuti; Ni Made Ida Pratiwi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Technology adaptation is key in the advancement of education in Indonesia. The existence of campus teaching programs has a lot of positive impacts on students, teachers and student teams. The implementation of the teaching campus is at SDN Kedungdoro V/310 Surabaya. Through qualitative methods, which start from the student debriefing stage to the assignment stage at the assignment school. Work programs that apply technology adaptation in the form of digital presence and flipbook-based digital libraries illustrate technological developments in increasing efficiency and effectiveness in recapping student attendance and creating an interesting learning process. The results of the activities that have been carried out encourage students to be enthusiastic in the learning process and provide new knowledge for teachers to better adapt to the current times and technology. As for the teaching campus student team, they can take action and change in the world of Education with current technological developments.